Carbon and nitrogen optimization in solid-state fermentation for sustainable sophorolipid production using industrial waste - Eras-Muñoz, Estefanía; Gea, Teresa; Font, Xavier (Frontiers in Bioengineering and Biotechnology, 2024)
The use of alternative feedstocks such as industrial or food waste is being explored for the sustainable production of sophorolipids (SLs). Microbial biosurfactants are mainly produced via submerged fermentation (SmF), however, solid-state fermentation (SSF) seems to be a promising alternative to take advantage of solid waste or byproducts that could not be exploited by SmF.Applying the advantages that SSF offers and with the aim of revalorizing industrial organic waste, the impact of carbon and nitrogen sources on the relationship between yeast growth and SL production was analyzed. The lab scale system used winterization oil cake as solid waste for hydrophobic carbon source. Pure hydrophilic carbon (glucose) and nitrogen (urea) sources were used in a Box-Behnken statistical design of experiments at different ratios by applying the response surface methodology. Optimal conditions to maximize the production and productivity of diacetylated lactonic C18:1 was a glucose/nitrogen ratio of 181.7:1.43 (w w -1 based on initial dry matter) at 100 h fermentation time, reaching 0.54 total g of diacetylated lactonic C18:1 with a yield of 0.047 g per g of initial dry mass. Moreover, time course fermentation with optimized conditions increased 22% the SL crude extract and 30% the diacetylated lactonic C8:1 (30%) production when compared to reference conditions. After optimization, industrial wastes were used to substitute pure substrates. Different industrial sludges, OFMSW hydrolysate and sweet candy industry wastewater provided nitrogen, hydrophilic carbon, and micronutrients allowing their use as alternative feedstocks for sophorolipids production. Sweet candy industry wastewater and cosmetic sludge are potential hydrophilic carbon and nitrogen sources, respectively, for sophorolipids production achieving yields around 70% when compared to the control group.